"Run to the hills": Specific contributions of anticipated energy expenditure during active spatial learning. Issue 12 (December 2022) - Lhuillier, Simon; Piolino, Pascale; Nicolas, Serge; Gyselinck, Valérie
Grounded views of cognition consider that space perception is shaped by the body and its potential for action. These views are substantiated by observations such as the distance-on-hill effect, described as the overestimation of visually perceived uphill distances. An interpretation of this phenomenon is that slanted distances are overestimated because of the integration of energy expenditure cues. The visual perceptual processes involved are, however, usually tackled through explicit estimation tasks in passive situations. The goal of this study was to consider instead more ecological active spatial processing. Using immersive virtual reality and an omnidirectional treadmill, we investigated the effect of anticipated implicit physical locomotion cost by comparing spatial learning for uphill and downhill routes, while maintaining actual physical cost and walking speed constant. In the first experiment, participants learnt city layouts by exploring uphill or downhill routes. They were then tested using a landmark positioning task on a map. In the second experiment, the same protocol was used with participants who wore loaded ankle weights. The results from the first experiment showed that walking uphill routes led to a global underestimation of distances compared with downhill routes. This inverted distance-of-hill effect was not observed in the second experiment, where an additional effort was applied. These results suggest that the underestimation of distances observed in Experiment 1 emerged from recalibration processes whose function was to solve the transgression of proprioceptive predictions linked with uphill energy expenditure. The results are discussed in relation to constructivist approaches on spatial representations and predictive coding theories.